Saving realist prudence - Stefano Guzzini (Danish Institute for International Studies (DIIS), 2019)
Samuel Barkin's "Realist Constructivism" has often been read as a way to synthesise realist theory and constructivist meta-theory. Guzzini argues that it is better understood as an attempt to combine realist foreign policy doctrine with constructivist theory. It is an invitation to explore constructivism as the theoretical backbone to inform a prudent foreign policy. Indeed, this DIIS Working Paper argues that a constructivist foreign policy doctrine informs realises the aim of prudence just as well, if not better, as realist maxims.
Keywords: 330; Realism; Constructivism; Prudence